2020
DOI: 10.1177/1352458520948231
|View full text |Cite
|
Sign up to set email alerts
|

Multiple sclerosis management during the COVID-19 pandemic

Abstract: Background: People with multiple sclerosis (MS) may be at higher risk for complications from the 2019 coronavirus (COVID-19) pandemic due to use of immunomodulatory disease modifying therapies (DMTs) and greater need for medical services. Objectives: To evaluate risk factors for COVID-19 susceptibility and describe the pandemic’s impact on healthcare delivery. Methods: Surveys sent to MS patients at Cleveland Clinic, Johns Hopkins, and Vall d’Hebron-Centre d’Esclerosi Múltiple de Catalunya in April and May 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 13 publications
(15 reference statements)
2
76
2
1
Order By: Relevance
“…The mean age of our patients was similar to that reported in a French study with 347 patients 3 and a study from New York city with 76 patients, 10 suggesting that patients with MS who are older and have more comorbidities undergo a stricter confinement. This hypothesis is supported by the association found between younger age of patients with COVID-19 with higher exposure to possible sources of infection, as reported in 2 large studies of MS conducted in Europe and the United States 11,12 and in a study of patients with rheumatic diseases treated with biological and synthetic diseasemodifying antirheumatic drugs carried out in Barcelona. 13 This fact, and more frequent medical consultation due to patients' concern of an increased risk associated with therapy, would explain the increased incidence of COVID-19 observed in our study.…”
Section: Discussionmentioning
confidence: 56%
“…The mean age of our patients was similar to that reported in a French study with 347 patients 3 and a study from New York city with 76 patients, 10 suggesting that patients with MS who are older and have more comorbidities undergo a stricter confinement. This hypothesis is supported by the association found between younger age of patients with COVID-19 with higher exposure to possible sources of infection, as reported in 2 large studies of MS conducted in Europe and the United States 11,12 and in a study of patients with rheumatic diseases treated with biological and synthetic diseasemodifying antirheumatic drugs carried out in Barcelona. 13 This fact, and more frequent medical consultation due to patients' concern of an increased risk associated with therapy, would explain the increased incidence of COVID-19 observed in our study.…”
Section: Discussionmentioning
confidence: 56%
“…Dr Moss commented in his recent observational study that the main risk factor for developing suspected or confirmed COVID‐19 was a known history of exposure, highlighting the importance of standard infection prevention measures 4 . In patients who have been stable on a DMT for a prolonged period, delaying routine magnetic resonance imaging for disease surveillance might help to avoid exposure.…”
Section: Factors To Consider In Dmt Decision‐making During the Covid‐mentioning
confidence: 99%
“…The panelists also acknowledged the indirect impacts of the COVID‐19 pandemic on MS patients. Dr Moss pointed out that 16% of patients at the Cleveland Clinic Mellen Center have had an interruption in rehabilitation services during the pandemic 4 . Many have also experienced increased stress, depressed mood, and decreased medical contact during the pandemic, reinforcing the need for clinicians to ask MS patients about other symptoms and medical screenings.…”
Section: Other Impacts Of the Covid‐19 Pandemic On Ms Patientsmentioning
confidence: 99%
“…Not least, the use disease-modifying treatments (DMTs), causing different degrees of systemic immunosuppression, might further affect the possibility of preventing and responding to the infection [ 5 ]. In line with this, healthcare providers and policy makers have immediately advised people with MS to self-isolate, and the use of immunomodulatory and immunosuppressive DMTs has been postponed [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, asymptomatic carriers can transmit the virus in the absence of obvious symptoms and could be responsible for keeping SARS-CoV-2 circulating [ 12 ]. As such, studying the prevalence of SARS-CoV-2 IgG/IgM in MS can shed light on the risk of COVID-19 infection in relation to MS and/or to the use of some DMTs, on the amount of patients who are still susceptible to infection, and on the possibility of asymptomatic carriers in MS, and can also be used to plan clinical activities accordingly [ 5 , 8 , 13 , 14 , 15 ]. Thus, in the present study, we aim to: (1) evaluate the prevalence of SARS-CoV-2 IgG/IgM antibodies in asymptomatic MS patients, compared with populations at low-risk and high-risk of COVID-19 infections; and (2) explore possible correlates with demographics, clinical features, treatments, comorbidities, and laboratory findings.…”
Section: Introductionmentioning
confidence: 99%